TEACHING THE ENGLISH ALPHABET TO VERY YOUNG LEARNERS IN PRE-SCHOOL INSTITUTIONS - Fazliddinova Zulfiyakhon Dilmurod qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Reading or writing is the leteracy skills that every one should learn and there are enough conditions for it. Teaching reading and writing is not a simple work to be done by teachers. While, it is preferred to teach reading and writing from the youngest ages of children. This study reviews the teaching methods and their efficiency in teaching the Alphabet to very young learners from 3-5 years old. As earlier a child learns to read, the faster he will acquire other significant skills in the language proficiency.